2019
DOI: 10.1177/0894845319837384
|View full text |Cite
|
Sign up to set email alerts
|

Examining Job Attribute Preferences Across Three Generational Cohorts

Abstract: This study examines whether job attribute preferences differ across three generational cohorts (i.e., cohorts of undergraduate students from 1995, 2004, and 2013). In 2013, we surveyed undergraduate students from several U.S. universities. We also obtained archival results from surveys administered to undergraduate students in 1995 and 2004. We found that salary/benefits, career advancement, and flexible work policies become more important across all three generational cohorts, whereas gender/racial equality i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…While multigenerational cohort studies or cross-generational studies have been detected in different areas of academic research, most of the studies focus on generational differences in the workplace [59][60][61]. Yet, other academic fields also encompass cross-generational differences, such as the travel and tourism industry [62][63][64][65]; the health, mental, cognition, or psychology sector examining related issues [66][67][68]; the service sector [69][70][71]; and studies in education [72,73].…”
Section: Literature Reviewmentioning
confidence: 99%
“…While multigenerational cohort studies or cross-generational studies have been detected in different areas of academic research, most of the studies focus on generational differences in the workplace [59][60][61]. Yet, other academic fields also encompass cross-generational differences, such as the travel and tourism industry [62][63][64][65]; the health, mental, cognition, or psychology sector examining related issues [66][67][68]; the service sector [69][70][71]; and studies in education [72,73].…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Sánchez-Hernández et al (2019) , an important aspect for the younger generations is to combine work and family life in such a way as to create a strong work-life balance. Further to this, the younger the generation, the more value is placed on work-life balance and relaxation and less value is place on work ethic and the importance of work to an employe’s life ( Lyons and Kuron, 2014 ; Brink and Zondag, 2019 ). Brink and Zondag (2019) also reported that the significance of flexible work-life policies increased across the generational cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that while generational differences remain rich and complex, and that assessing commonalities and differences across generations is worthy of study, all generations of workers share a similar goal of developing and becoming themselves in the workplace. Indeed, employees expect their employer's values to be in alignment with their own, have occasion to take part in decision making, as well as have challenging work influence meaningfulness and hinder workers' inclinations to quit [21,44,74] A cross-sectional study was conducted to examine meaningful work across generations and their influence on work engagement. While results revealed significant differences between Baby Boomers, GenXers, and Baby Boomers, and Millennials, they found no differences between GenXers and Millennials [1].…”
Section: Discussionmentioning
confidence: 99%